Analysis of Ethnoscience Concepts and Early Childhood Character Formation in Sundanese Folklore - Dewiantika Azizah; Dede Latipah; Lucky Dewanti; Heru Wardany (Universitas Sebelas Maret, 2025)
Various natural phenomena that appear in Sundanese folklore continue to roll into legends that provide knowledge in the form of moral values embedded in the thinking of Sundanese society. Moral values are formed into a value of local cultural wisdom that can be integrated with science into a new scientific concept known as Ethnoscience. This study aims to analyse the idea of ethnoscience and character building in Sundanese folklore. This research uses descriptive qualitative methods with an ethnoscience approach. The research method examined the concept of natural events and character building in Sundanese folklore. The data analysis process uses an interactive analysis model, going through the stages of data reduction, data presentation, and conclusion drawing. The results showed the analysis of several ethnoscience concepts in the form of the formation process: (a) Situ Bagendit, (b) Mount Tangkuban Perahu, and (c) Telaga Warna, which are integrated with the value of local wisdom that emerges from each Sundanese folklore. The value of local wisdom formed in each Sundanese folklore stimulates character building because of the content of moral values, which results from the negative actions of the character.